Unveiling financial well-being: Insights from retired people in Third Age group in Poland, Spain and Denmark - Jajko-Siwek, Alicja (Economics and Business Review, 2024)
The study investigates the financial well-being of older people in Poland, Spain and Denmark, with a particular focus on their ability to make ends meet. Using data from the SHARE survey to analyse retired individuals aged 65 to 79 years, it aims to identify the socio-economic factors that influence financial well-being among older people in these countries. In terms of methodology, it uses Light Gradient Boosting Machine algorithm and SHAP value calculations to predict the ability to make ends meet and determine the importance of 167 various features. The study concludes that household income and financial resources are the primary determinants of older people’s ability to make ends meet. The findings underscore the need for policymakers and practitioners the fields of ageing and economics to address specific challenges, such as housing costs in Denmark and food expenditure in Poland and Spain, to improve the financial well-being of older individuals.